Analysis and research on propagation field strength characteristics of non-line-of-sight signal - Fengxun GONG; Ying ZHANG (Dianxin kexue)
In order to explore the diffraction loss caused by non-line-of-sight (NLOS ) propagation caused by obstacles in the airport communication path, the attenuation characteristics of signal field were studied.Firstly, based on the influence of different terrain environments on signal propagation in ITU-R P.1546, a combined signal field strength model was constructed with Deygout model.Secondly, according to the number of obstacles, the propagation characteristics of the received field strength varying with the height of obstacles were analyzed.The simulation results show that the higher the single obstacle is, the larger the Fresnel zone occupying 0.6F1 is and the smaller the field strength is.In the dual obstacle path, the obstacle with increased height goes through the process of changing from secondary to main obstacle until only the main obstacle is left, so that the field strength gradually decreases.Thirdly, the relationship between secondary obstacle height and 0.6F1 Fresnel zone was analyzed for field strength rise.Finally, the minimum threshold of the covered field strength was adjusted to determine whether the receiving device was blocked by obstacles and the signal was shielded.The above research results can provide a reference for simulating the distribution of obstacles in various airport scenarios in the future, and predicting whether the receiver is interfered by obstacles or affects the field intensity coverage.